Strategi Komunikasi Branding PT. Kartel Daun International dalam Bisnis Ekspor Tanaman Hias - Amin, Mohammad Rahul; Hapsari, Hepi (Universitas Galuh, 2026)
ABSTRACTPT. Kartel Daun International as an ornamental plant exporters, faces several challenges, including limited human resources and the reliance on a single communication platform, which potentially restricts its global market reach. This study aims to analyze the company’s communication strategy in branding the ornamental plant export business and to identify internal and external factors affecting its implementation. The research employed a qualitative descriptive method with a case study approach. Data were collected through observation, interviews, documentation, and literature study. Data analysis was conducted using NVivo. The results indicate that PT. Kartel Daun International applies a two-way communication strategy focused on customers, referring to five communication components: communicator (internal team and KOL), message (branding, educational, product information, and promotion), media (Instagram, Facebook, TikTok, website, and exhibitions), communicant (international customers), and effect (increased credibility and creation interest). Internal strengths include skilled human resources, consistent communication, and customer convenience. Weaknesses consist of channel dependency, limited promotional budget, and insufficient staff. Opportunities involve exploring new media, engaging Key Opinion Customers (KOC), and reaching new markets. Threats include growing competitors, dominance of other platforms, and potential negative reviews. Communication success relies on strong understanding and responsiveness to customer needs.